2018
DOI: 10.3171/2017.9.jns171321
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diffusion tensor imaging tractography to visualize the dentatorubrothalamic tract for surgical planning

Abstract: OBJECTIVE The dentatorubrothalamic tract (DRTT) has been suggested as the anatomical substrate for deep brain stimulation (DBS)-induced tremor alleviation. So far, little is known about how accurately and reliably tracking results correspond to the anatomical DRTT. The objective of this study was to systematically investigate and validate the results of different tractography approaches for surgical planning. METHODS The authors retrospectively analyzed 4 methodological approaches for diffusion tensor imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Thalamotomy for tremor is aimed to impact on the anatomical connections within the cerebello‐thalamo‐cortical system, specifically the DRTT, stopping the tremor activity from propagating from the cerebellum to the motor cortex. Using tractography it is possible to define the anatomical boundaries of this tract (Akram et al, ; Meola, Yeh, Fellows‐Mayle, Weed, & Fernandez‐Miranda, ; Nowacki, Schlaier, Debove, & Pollo, ), and so the number of studies encouraging the tractography‐based segmentation of the DRTT for targeting in either thalamotomy or DBS is growing (Akram et al, ; Coenen et al, ; Sammartino et al, ; Tian et al, ; Tsolaki, Downes, Speier, Elias, & Pouratian, ). Our results are in line with these studies, and suggest that tractography based guidance during tcMRgFUS treatment strategy could be very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamotomy for tremor is aimed to impact on the anatomical connections within the cerebello‐thalamo‐cortical system, specifically the DRTT, stopping the tremor activity from propagating from the cerebellum to the motor cortex. Using tractography it is possible to define the anatomical boundaries of this tract (Akram et al, ; Meola, Yeh, Fellows‐Mayle, Weed, & Fernandez‐Miranda, ; Nowacki, Schlaier, Debove, & Pollo, ), and so the number of studies encouraging the tractography‐based segmentation of the DRTT for targeting in either thalamotomy or DBS is growing (Akram et al, ; Coenen et al, ; Sammartino et al, ; Tian et al, ; Tsolaki, Downes, Speier, Elias, & Pouratian, ). Our results are in line with these studies, and suggest that tractography based guidance during tcMRgFUS treatment strategy could be very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was hypothesized that the mentioned target regions (Vim, STR, cZI) are actually confluent with the DRT which is hit in different (thalamic and subthalamic) parts ("three stereotactic targets, one fiber pathway" concept) [13,14]. Several groups have since used DTI tractography to modulate the DRT in DBS surgery [3,19,21,57,60] and have meticulously refined targeting strategies with good results [43]. Moreover, evidence for DRT as being a marker structure for the identification of the Vim at MCP level has been reported on stimulation grounds [14,57] and based on related intraoperative electrophysiology [29].…”
Section: Introductionmentioning
confidence: 99%
“…Akram and colleagues found, in a small series of ET and PD patients, that greater VTA overlap with the DRTC was present in patients with better tremor control . In contradiction, Nowacki and colleagues was unable to reproduce the findings of greater tremor improvement with DRTC stimulation using four different tractography methods . As opposed to the previously discussed ET studies, which used patient‐specific data, Al Fatly and colleagues found similar connectivity associated with VTAs in the posterior subthalamic area, and these VTAs correlated with greater improvement in tremor when using normative connectome data …”
Section: Etmentioning
confidence: 95%
“…Other studies have highlighted the tremor suppression associated with stimulation of the DRTC—a fiber tract that connects the dentate nucleus with the red nucleus, thalamus, and PMC . Akram and colleagues found, in a small series of ET and PD patients, that greater VTA overlap with the DRTC was present in patients with better tremor control .…”
Section: Etmentioning
confidence: 99%